Manager of financial globalization? The European Union in global anti-money laundering and international accounting standard setting - Sven Hilgers (Freie Universität Berlin, Center for International Political Economy, 2014)
How does the European Union (EU) perform in international financial regulation? According to various scholars the global financial architecture has been shaped by the USA and the EU. But whereas the USA is without doubt the dominant actor or even described as hegemon in writing the rules for the global political economy and global financial markets, the EU seems to be a special kind of actor. The European Union is not only one of the biggest single financial markets in the world but also has become one of the largest financial jurisdictions in the last decade. Despite this huge market size the EU's representation in institutions of the global financial regulation is quite low. Hence the direct EU impact on global financial regulation is often seen as weak or the EU is perceived rather as a forum than an actor. Given the debate on the external actorness of the EU global financial regulation is an interesting case for evaluating the EU's actorness in fields, where the EU has competences like anti-money laundering and setting accounting standards. In the paper I applied the managed globalization doctrine in order to analyze the EU's performance in those fields. The evidence illustrates that even in the fields, where the EU have regulatory competencies, the European Union is not able or willing to shape the global regulation. – – Welchen Einfluss hat die Europäische Union (EU) in internationaler Finanzmarktregulierung? Zahlreiche Wissenschaftler gehen davon aus, dass die globale Finanzarchitektur maßgeblich von den USA und der EU geprägt worden ist. Während aber die USA zweifelsohne der zentrale Akteur, vielleicht sogar ein Hegemon in der globalen Finanzmarktregierung ist, scheint die EU ein spezieller Akteur zu sein. Die EU besitzt nicht nur den größten Finanzmarkt der Welt, sondern ist auch zu einem der größten einheitlich geregelten Märkte der Welt geworden. Doch trotz dieser Marktgröße ist die EU in den zentralen Institutionen zur Regulierung von Finanzmärkten nicht vertreten. Gerade auch deswegen wird der direkte Einfluss der EU auch meistens als schwach eingestuft. Vor dem Hintergrund der laufenden Debatte über die Akteursqualität der EU ist die globale Finanzmarktregulierung ein interessanter Fall, um die Akteursqualität der EU in Feldern zu untersuchen, in denen sie Regulierungskompetenz hat. In den Bereichen Geldwäschebekämpfung und Bilanzierungsstandards hat die EU Kompetenzen. Daher wird in dem vorliegenden Papier anhand der "Managed Globalization" Doktrin untersucht, inwiefern die EU in der Lage ist als eigenständiger Akteur zu agieren. Die Ergebnisse der Studie geben ein ernüchterndes Bild wieder. In keinem der beiden Fälle ist die EU in der Lage oder Willens, die Regulierung wirksam zu beeinflussen.
urn:nbn:de:101:1-2014120322411
Keywords: 330